Đặc điểm đứt gãy hoạt động và tai biến nứt đất dọc đường Hồ Chí Minh, đoạn từ Tây Giang đến Phước Sơn (tỉnh Quảng Ngãi) - Hùng, Phạm Văn (Vietnam Journal of Earth Sciences, 2012)
SUMMARY The characteristics of active faults and land cracking hazard along Tay Giang - Phuoc Son section of the Ho Chi Minh route, Quang Nam Province The Tay Giang - Phuoc Son section of Ho Chi Minh route locates at an active tectonic area. Active faulting is one of the main causes which are responsible for land cracking hazard in the route. - In the section, land cracking hazard can be observed at 18 sites, some locations were seriously damaged such as : A Tep, Za Hung, Ma Cooih, Phuoc Xuan, Song Bung pass and Lo Xo pass,... - Land cracking hazard sites of the Ho Chi Minh route - bed locate on crosscut between the route and active faults. Fracture sets of “en-echelon” tention cracks show systematic displacements of tectonic faults: normal-left slip of the NE-SW faults and normal-right strike slip of the NW-SE ones. - In the recent geodynamic setting with submeridian compression, some active faults such as A Den - Ai Nghia, Phuoc Xuan - Tam Ky, Song Bung - Tra Bong, Po Ko River, Con River,... caused route-bed damage and land cracking hazard at the crosscut with Ho Chi Minh route